SENSORY ANALYSIS OF INSTANT COMPLEMENTARY FOOD WITH FERMENTED EGG FLOUR SUBSTITUTION AS A SOURCE OF PROTEIN AND SELENIUM IN STUNTING CHILDREN - Dewi, Sonia Kurnia; Fadhila, Farah Rosyihana; Nuryanto; Margawati, Ani; Sugiharto; Rustanti, Ninik; Ayustaningwarno, Fitriyono (Universitas Airlangga, 2025)
Childhood stunting is a health problem associated with chronic malnutrition, particularly inadequate protein and selenium intake. Fermented egg flour was chosen because the fermentation process can increase the bioavailability of protein and selenium. This study aimed to develop and evaluate the sensory quality of instant complementary food formulated with fermented egg flour as a source of protein and selenium. The nutritional composition of this formulation has been reported in a previous study; therefore, this research specifically focuses on its sensory evaluation. The sensory test was conducted using a 9-scale hedonic method on the parameters of taste, aroma, texture, and color involving 66 semi-trained panelists (nutrition students). The research method used a completely randomized design (CRD) with four formulations: F0 (control) and F1, F2, and F3 as treatments with 10, 15 and 20% fermented eggs, respectively. Data analysis used one-way ANOVA and Kruskal-Wallis tests (p<0.05). The test results showed that the substitution of fermented egg flour had a significant effect on panelists' preferences in the aspects of color, taste, and aroma but not significant in texture; the protein content from 20.56% to 20.59%, 21.68%, and 22.54%, along with an increase in energy content from 417 kcal to 419 kcal, 427 kcal, 431 kcal in instant complementary food. However, higher fermented egg flour proportions reduced acceptance due to a fishy aroma.